Berpikir atau Bergantung? Fenomena Cognitive Offloading pada Mahasiswa Pengguna AI di Era Society 5.0 - Nisa Arfiana Nurbaeti; Tesa Nurul Huda (UM Purwokerto Press, 2026)
The development of artificial intelligence (AI) in education has transformed the way students access information and complete academic activities in the Society 5.0 era. However, this convenience has also given rise to the phenomenon of cognitive offloading, namely the tendency of individuals to transfer part of their thinking processes to technology. This essay aims to analyze the phenomenon of cognitive offloading among students using AI from the perspectives of cognitive psychology and neuroscience, as well as examine its implications for modern learning processes. The method used is a literature study by reviewing various studies related to AI, cognitive offloading, working memory, and prefrontal cortex functions. The findings indicate that excessive AI use may reduce students’ cognitive engagement, trigger passive cognition, and weaken critical thinking and problem-solving abilities. In addition, cognitive offloading is associated with decreased stimulation of working memory and prefrontal cortex activity due to the dominance of instant answers provided by technology. Therefore, the use of AI in education should be directed as a cognitive partner rather than a cognitive replacement through the strengthening of metacognitive AI literacy and learning approaches oriented toward reflective thinking processes.